Unveiling the mechanisms driving the rapid growth of Malania oleifera seedlings, a high-value root hemiparasitic plant - Si-Hai Wang; Si-Hai Wang; Chuan-Guang Zhang; Chuan-Guang Zhang; Wei Yang; Wei Yang; Jian Chen; Jian Chen; Ming Shi (Frontiers in Plant Science, 2025)
Certain root hemi-parasitic tree species hold significant economic value, yet they are challenging to cultivate artificially. Therefore, understanding how soil conditions and host plants influence the growth of these species is crucial. The endemic tree species Malania oleifera, native to the karst landscapes of southwest China, is highly valued for its seed oil, rich in nervonic acid. As a root hemiparasite, M. oleifera presents challenges for artificial cultivation, making it crucial to improve seedling survival and develop effective propagation methods for this and similar species. We used nutrient-rich and nutrient-deficient growth substrates, combined with four planting configurations involving host and non-host plants, to monitor the growth of M. oleifera seedlings. We then analyzed the transcriptomic differences between non-parasitic and parasitic plants that exhibited significant growth disparities. Vigorous host plants significantly enhance the growth of M. oleifera seedlings, while soil conditions exert a weaker influence. The host primarily promotes aboveground M. oleifera growth, with only limited impact on root development, resulting in an imbalance between the two. Endogenous hormone levels in the haustoria connected to the host exhibit substantial changes, with notable upregulation of genes related to hormone metabolism, stress responses, and antibiotic biosynthesis. Furthermore, the roots of host-associated M. oleifera seedlings show heightened responses to both biotic and abiotic stresses, along with key metabolic processes. An appropriate host enhances the overall adaptability, nutrient synthesis, and stress resistance of M. oleifera seedlings, all of which are essential for their growth, development, and survival.